The UTMOST pulsar timing programme – II. Timing noise across the pulsar population. Issue 1 (4th March 2020) - Lower, M E; Bailes, M; Shannon, R M; Johnston, S; Flynn, C; Osłowski, S; Gupta, V; Farah, W; Bateman, T; Green, A J; Hunstead, R; Jameson, A; et al.
ABSTRACT: While pulsars possess exceptional rotational stability, large-scale timing studies have revealed at least two distinct types of irregularities in their rotation: red timing noise and glitches. Using modern Bayesian techniques, we investigated the timing noise properties of 300 bright southern-sky radio pulsars that have been observed over 1.0–4.8 yr by the upgraded Molonglo Observatory Synthesis Telescope ( MOST ). We reanalysed the spin and spin-down changes associated with nine previously reported pulsar glitches, report the discovery of three new glitches and four unusual glitch-like events in the rotational evolution of PSR J1825−0935. We develop a refined Bayesian framework for determining how red noise strength scales with pulsar spin frequency (ν) and spin-down frequency (ν ), which we apply to a sample of 280 non-recycled pulsars. With this new method and a simple power-law scaling relation, we show that red noise strength scales across the non-recycled pulsar population as ν ^a |ν |^b, where a = -0.84^+0.47_-0.49 and b = 0.97^+0.16_-0.19 . This method can be easily adapted to utilize more complex, astrophysically motivated red noise models. Lastly, we highlight our timing of the double neutron star PSR J0737−3039, and the rediscovery of a bright radio pulsar originally found during the first Molonglo pulsar surveys with an incorrectly catalogued position.